Fertilizer Application Best Management Practices for Citrus Grove Workers - Brian Boman; Darren Cole; Steve Futch; Ward Gunter; Jack W. Hebb; P. Chris Wilson (EDIS, 2010)
Revised! AE248, a 12-page fact sheet by Brian Boman, Darren Cole, Steve Futch, Ward Gunter, Jack Hebb, and Chris Wilson, instructs citrus grove workers in fertilizer application best management practices. Includes references and quizzes throughout. Published by the UF Department of Agricultural and Biological Engineering, March 2009.